Implementation of the GRIN solid immersion lens - Hsieh, Chih-Hung (2013)
A gradient-index solid immersion lens is fabricated to approximate a distribution of refractive index matching derived from transformation optics. The simulation result has shown reduction of the ghost image and increase of the magnifying area.